GAMBARAN DAN PERMASALAHAN CAPAIAN ASI EKSKLUSIF DI PUSKESMAS OLAK KEMANG TAHUN 2023 - Yeni, Fitri (Scientific Of Environmental Health and Diseases, 2024)
ABSTRACTBackground:The proportion of exclusive breastfeeding in the work area of the Olak Kemang Health Center in2023 is 51.85% while the achievement target in Jambi City is 85%. For this reason, researchers want to know andidentify the achievement problems of exclusive breastfeeding in the work area of the Olak Kemang Health Centerin 2023.Objective:This research was conducted to find out the description and problems of achieving exclusivebreastfeeding at the Olak Kemang Health Center in 2023Method: This research was conducted in the work area of the Olak Kerja Health Center using a mix method in theform of interviews and questionnaires. Interviews were conducted with the head of the puskesmas and the officerin charge and questionnaires were given to mothers who visited posyandu, immunization and the IMCI polyclinicat the Olak Kemang Health CenterResults: Of the 30 respondents, it was shown that the frequency of babies who received exclusive breastfeedingfor 0-6 months was 8 people, namely 26.7%, while babies who did not get exclusive breastfeeding for 0-6 monthswere 22 people, 73.3%. Influenced by husband's support (66.7%), lack of family support (56.7%), support fromhealth workers (63.3%), mother's obstacles in breastfeeding (60.0%), and supportive mother's attitude (56.7 %)Conclusion:In this study, it was found that the prioritized problem was the achievement of exclusive breastfeedingat the Olak Kemang Health Center, namely 51.85%.Keywords: Exclusive breastfeeding, Health Center, Jambi